Development of Nasonia vitripennis (Hymenoptera: Pteromalidae) at Constant Temperatures in China. Issue 2 (1st November 2018) - Zhang, Yingna; Wang, Yu; Liu, Chang; Wang, Jiangfeng; Hu, Guoliang; Wang, Man; Yang, Lijun; Chu, Jun
Abstract: Nasonia vitripennis (Walker) (Hymenoptera: Pteromalidae) is a common ectoparasitoid that attacks the puparia of fly species of forensic importance, including blow flies, flesh flies, and house flies. The developmental time of N. vitripennis can be added to the host development time, providing the potential for an extended minimum postmortem interval timeframe in cases where traditional dipteran larval forensic timeline indicators have completed their development. In this study, we used Boettcherisca peregrina Robineau-Desvoidy (Diptera: Sarcophagidae) as the host for N. vitripennis and studied the development of N. vitripennis at seven constant temperatures between 16 and 34°C. The developmental process was divided into 12 periods, and we measured developmental time, changes in larval body length, and thermal requirements for development, including developmental thresholds and thermal constant. Using these data, we created an isomorphen diagram and thermal summation model of N. vitripennis . The total developmental duration of parasitoids from egg to adult emergence at 16, 19, 22, 25, 28 and 31°C were 953.3 ± 20.0, 698.0 ± 7.7, 508.7 ± 13.6, 354.7 ± 4.6, 272.0 ± 13.9, and 232.0 ± 11.3 h, respectively. Nasonia vitripennis did not emerge at 34°C. The developmental threshold temperature of N. vitripennis was 11.52°C, and the thermal summation constant was 4768.8 degree hours.